O-GlcNAcylation Suppresses the Ion Current IClswell by Preventing the Binding of the Protein ICln to α-Integrin - Costa, Roberta; Remigante, Alessia; Civello, Davide A.; Bernardinelli, Emanuele; Szabó, Zoltán; Morabito, Rossana; Marino, Angela; Sarikas, Antonio; Patsch, Wolfgang; Paulmichl, Markus; Janáky, Tamás; Miseta, Attila; et al. (Frontiers in Cell and Developmental Biology, 2020)
O-GlcNAcylation is a post-translational modification of proteins that controls a variety of cellular processes, is chronically elevated in diabetes mellitus and may contribute to the progression of diabetic complications, including diabetic nephropathy. Our previous work showed that increases in the O-GlcNAcylation of cellular proteins impair the homeostatic reaction of the regulatory volume decrease (RVD) after cell swelling by an unknown mechanism. The activation of the swelling-induced chloride current IClswell is a key step in RVD, and ICln, a ubiquitous protein involved in the activation of IClswell, is O-GlcNAcylated. Here we show that experimentally increased O-GlcNAcylation of cellular proteins inhibited the endogenous as well as the ICln-induced IClswell current and prevented RVD in a human renal cell line, while decreases in O-GlcNAcylation augmented the current magnitude. In parallel, increases or decreases in O-GlcNAcylation respectively weakened or stabilized the binding of ICln to the intracellular domain of α-integrin, a process that is essential for the activation of IClswell. Mutation of the putative Yin-O-Yang site at Ser67 rendered the ICln-induced IClswell current unresponsive to O-GlcNAc variations, and the ICln interaction with α-integrin insensitive to O-GlcNAcylation. In addition, exposure of cells to a hypotonic solution reduced the O-GlcNAcylation of cellular proteins. Together, these findings show that O-GlcNAcylation affects RVD by influencing IClswell, and further indicate that hypotonicity may activate IClswell by reducing the O-GlcNAcylation of ICln at Ser67, therefore permitting its binding to α-integrin. We propose that disturbances in the regulation of cellular volume may contribute to disease in settings of chronically elevated O-GlcNAcylation, including diabetic nephropathy.